2004
DOI: 10.1007/s00405-004-0818-9
|View full text |Cite
|
Sign up to set email alerts
|

Histological features and malignant transformation of inverted papilloma

Abstract: Inverted papilloma (IP) is a primarily benign epithelial neoplasm with a propensity to transform to squamous cell carcinoma (SCC). Neither the etiology of IP nor the factors responsible for malignant transformation are fully known to date. A considerable number of histopathological grading systems have been suggested. It was the aim of this study to find histological parameters in IP that allow a prognosis concerning the occurrence of malignant transformation. In a group of 93 cases of IP, the patients' record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 26 publications
0
27
1
4
Order By: Relevance
“…The malignant alteration of IPs has been widely recognized [1,4,8,22,23,[42][43][44][59][60][61][62][63][64][65]. Of all carcinomas associated with IPs, 61% are synchronous and 39%, metachronous [66].…”
Section: Discussionmentioning
confidence: 99%
“…The malignant alteration of IPs has been widely recognized [1,4,8,22,23,[42][43][44][59][60][61][62][63][64][65]. Of all carcinomas associated with IPs, 61% are synchronous and 39%, metachronous [66].…”
Section: Discussionmentioning
confidence: 99%
“…Eggers et al [6] reported a retrospective analysis of 93 cases and Katori et al [7] analysed a series of 39 cases of inverted papilloma to establish histological parameters to predict recurrence and malignant transformation. Multiple recurrences without malignancy were related to frontal sinus site, increased hyperkeratosis, presence of squamous epithelial hyperplasia, and increased mitotic index.…”
Section: Discussionmentioning
confidence: 99%
“…The factors which are responsible for this malignant transformation are as yet not understood. A number of studies have been performed in an attempt to discover predictive characteristics for malignant change [28,29]. Eggers et al [28] studied 93 cases of inverted papilloma with regards to both patient and tumor characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have been performed in an attempt to discover predictive characteristics for malignant change [28,29]. Eggers et al [28] studied 93 cases of inverted papilloma with regards to both patient and tumor characteristics. They concluded that certain histological features, namely increased mitotic count and dyscariosis, along with male gender and older age group put patients at a higher risk of malignant change.…”
Section: Discussionmentioning
confidence: 99%